Platelet rich fibrin versus ozone gel for periodontal regeneration in induced rats' intrabony three-wall periodontal defects - Alsherif, Aya Anwar (J Oral Biol Craniofac Res, 2020)
BACKGROUND: The question of whether platelet rich fibrin and ozone can enhance regeneration of periodontal defect was addressed. MATERIALS AND METHODS: three-wall periodontal defects were surgically created in 30 rats involving mesial aspect of right mandibular first molar. Rats were randomly assigned into three groups: 1) Group I (Positive control group). 2) Group II (Ozone treated group) and 3) Group III (PRF treated group). Two weeks after surgery, five rats from each group were euthanized and the remaining was euthanized 4 weeks post surgery. The degree of periodontal regeneration was evaluated using light microscope and scanning electron microscope. Histomorphometric measurements and anti-PCNA immunohistochemical counting were statistically analyzed. RESULTS: group I showed intense inflammatory reaction with mild new bone formation. In group II, partial regeneration was seen with moderate new woven bone formation in 2 weeks period. After 4 weeks, almost complete restoration of periodontium was seen. In group III, after 2 weeks, moderate lamellar bone formation was observed. In 4 weeks period, the periodontal regeneration was almost completed. Histomorphometric analysis showed a significant difference between group I and group II. The difference between group I and group III was significant in 2 weeks and highly significant after 4 weeks. That between group II and group III was nonsignificant in 2 weeks and significant in 4 weeks. Anti-PCNA analysis was nonsignificant between groups. CONCLUSIONS: both Platelet rich fibrin and ozone can improve histological parameters associated with healing of experimental intrabony periodontal defects in rats with the former being superior.